The Zero Interest Rate Floor (ZIF) and its Implications for Monetary Policy in Japan - Laxton, Douglas (IMF Working Papers; Working Paper ;, 2001)
This paper uses the IMF's macroeconomic model MULTIMOD to examine the implications of the zero-interest-rate floor (ZIF) for the design of monetary policy in Japan. Similar to findings in other studies, targeting rates of inflation lower than 2.0 percent significantly increases the likelihood of the ZIF becoming binding. Systematic monetary policy strategies that respond strongly to stabilize output and inflation, or that incorporate some explicit price-level component, can help to mitigate the implications of the ZIF.